Oxidative and nitrosative stres in some risk factor of stroke - Hasyim Fachir Hasyim Fachir (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Stroke is a disease caused by cerebral blood flow disturbance. Disturbance of cerebral blood flow could induce oxidative and nitrosative stres. Beside that, stroke is a also neurodegenerative disease that based on several risk factors. Some risk factors of stroke have causative link with oxidative and nitrosative stres. These risk factors include aging, hypertension, smoking, atherosclerosis and diabetes mellitus. Key words: stroke - risk factor -reactive oxygen species - reactive nitrogen species